Microplastic pollution and associated trace metals in freshwater ecosystems within protected natural areas: the case of a biosphere reserve in Mexico - Granados-Sánchez, Rubén Rafael; Sedeño-Díaz, Jacinto Elías; López-López, Eugenia (Frontiers in Environmental Science, 2024)
Microplastics (MPs) are considered pollutants of emerging concern. In rivers, MPs (≤5 mm) are transported by currents and deposited in lakes, reservoirs, estuaries, and oceans. In Mexico, MPs in freshwater ecosystems have been scarcely studied. This work aimed to determine the presence of MPs in rivers of the Sierra Gorda Biosphere Reserve (SGBR). Samples of surface water and sediment collected from the Escanela, Jalpan, Ayutla, and Santa María rivers were processed. MPs in water were extracted by direct filtration using nitrocellulose filters with a 1.2 μm pore size; MPs in sediments were extracted by density suspension using a ZnCl2 solution (ρ ≈ 1.5 g/cm 3 ). The surface of MPs was examined using SEM-EDX, and spectra of trace elements deposited on the MPs were obtained; additionally, MP polymers were characterized with FTIR. Fibers were the most abundant MP forms in both matrices. Up to 110.87 MP items L -1 were detected in water and 175 items kg -1 (dry weight) in sediments. Surface wear of MPs was observed, and trace elements were detected, including Al, Fe, Cr, Si, and Zn, among others. The polymers identified in MP samples were polyethylene terephthalate, polyester, polypropylene, high-density polyethylene, polyamide, and polystyrene. The test results revealed the presence of MPs with trace metals on their surface in the freshwater ecosystems of the SGBR, which may be related to mining operations in the study area, changes in land use, wastewater discharges, atmospheric transport, and dry and wet deposition. These findings demonstrated the ubiquity of these pollutants and their presence even in areas intended for conservation.